Theories of the Welfare State in Contemporary Historiography - Rákosník, Jakub (Dějiny – teorie – kritika, 2009)
This article focuses on the theory of the welfare state and its use in historical research. The first part considers two classic interpretational approaches used in sociology, system theory and conflct theory, and also their main shortcomings. Systems-theory approaches to the interpretation of welfare states usually exhibit a dependence on a metanarrative of the understanding of history as displayed by the proponents of progress. The welfare state is thus largely understood as a necessary consequence of the modernization of society. An advantage of this approach, on the other hand, is the endeavour to achieve a universalistic conception of historical interpretation, including the practices of different cultures throughout the world. Conflict theory effectively describes struggle and tension in society, the result of which may be the achievement of the recognition of fundamental social rights. On the other hand, it has a tendency to underestimate systemic factors, which are not connected with the aggregation of interests and their representation in the social system. New interpretational trends in social historiography, particularly gender history, the study of governmentality, and the analysis of discourse, point to the shortcomings of these traditional approaches. Though they have at their disposal great critical potential and are able to raise neglected questions of the history of social states, these approaches do not offer a basis for similarly broad comparative historical research in system theory or conflict theory.